Volenti non fit iniuria - Anderson, Ian (Department of Private Law, 2023)
The topic of this dissertation is primarily concerned with evaluating the practical and jurisprudential merits of the modern principle of volenti non fit iniuria as it is applied in the context of the South African Delictual Law on patrimonial loss. Though a similar evaluation of the volenti doctrine in respect to the modern Actio Iniuriarum .falls outside the scope of this dissertation, reference will also be made to the Valenti defence in that context.